Peran Orang Tua melalui PAK dalam Keluarga terhadap Pengaruh Negatif Gadget pada Remaja di Jemaat Gmim Theodoron Tateli Wilayah Mandolang I - Tarumingi, Denny A.; Koraag, Ilvi (LP. Ma'arif Janggan Magetan, 2024)
Christian religious education in the family is education that aims to teach children the faith and as the first place to spread the Word of God, both through teaching and example in life. Nowadays, almost all groups, especially teenagers, are influenced by gadgets, where this gadget is a communication tool that has many different functions and properties and is considered more complete than other communication tools. Almost every teenager who uses gadgets spends a lot of time a day using gadgets so that this affects their behavior in the family. Therefore, this research aims to find out the role of parents through Christian religious education in the family on the negative influence of gadgets on teenagers. The research is based on changes in adolescent behavior due to excessive use of gadgets. The research uses a qualitative approach with descriptive methods. Data was obtained through observation and in-depth interviews with parents and teenagers who use gadgets at the Theodoron Tateli Congregation, especially teenagers.